Risk of colectomy after conservative treatment of diverticulitis of the left hemicolon complicated by abdominal or pelvic abscess: protocol of a systematic review and meta-analysis - Helmut Friess; Maximilian Sohn; Ayman Agha; Igors Iesalnieks; Alfred Hochrein; Anna Tiefes; Dirk Wilhelm; Stephan Schorn (BMJ Open)
Introduction Acute diverticulitis of the sigmoid colon is increasingly treated by a non-operative approach. The need for colectomy after recovery from a flare of acute diverticulitis of the left colon, complicated diverticular abscess is still controversial. The primary aim of this study is to assess the risk of interval emergency surgery by systematic review and meta-analysis.Methods and analysis The systematic review and meta-analysis will be conducted in accordance to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols statement. PubMed/MEDLINE, Cochrane Central Register of Controlled Trials and EMBASE will be screened for the predefined searching term: (Diverticulitis OR Diverticulum) AND (Abscess OR pelvic abscess OR pericolic abscess OR intraabdominal abscess) AND (surgery OR operation OR sigmoidectomy OR drainage OR percutaneous drainage OR conservative therapy OR watchful waiting). All studies published in an English or German-speaking peer-reviewed journal will be suitable for this analysis. Case reports, case series of less than five patients, studies without follow-up information, systematic and non-systematic reviews and meta-analyses will be excluded. Primary endpoint is the rate of interval emergency surgery. Using the Review Manager Software (Review Manager/RevMan, V.5.3, Copenhagen, The Nordic Cochrane Centre, The Cochrane Collaboration, 2012) meta-analysis will be pooled using the Mantel-Haenszel method for random effects. The Risk of Bias in Non-randomized Studies of Interventions tool will be used to assess methodological quality of non-randomised studies. Risk of bias in randomised studies will be assessed using the Cochrane developed RoB 2-tool.Ethics and dissemination As no new data are being collected, ethical approval is exempt for this study. This systematic review is to provide a new insight on the need for surgical treatment after a first attack of acute diverticulitis, complicated by intra-abdominal or pelvic abscesses. The results of this study will be presented at national and international meetings and published in a peer-reviewed journal.PROSPERO registration number CRD42020164813.